2013
DOI: 10.1111/gbb.12049
|View full text |Cite
|
Sign up to set email alerts
|

Progress in understanding mood disorders: optogenetic dissection of neural circuits

Abstract: Major depression is characterized by a cluster of symptoms that includes hopelessness, low mood, feelings of worthlessness and inability to experience pleasure. The lifetime prevalence of major depression approaches 20%, yet current treatments are often inadequate both because of associated side effects and because they are ineffective for many people. In basic research, animal models are often used to study depression. Typically, experimental animals are exposed to acute or chronic stress to generate a variet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
75
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(78 citation statements)
references
References 175 publications
3
75
0
Order By: Relevance
“…Conversely, the second study showed the opposite effects where phasic activity of VTA DA neurons rescued stress-induced depressive-like behaviour in mice that had undergone chronic mild stress [168]. The discrepancy between the two studies has been discussed [176, 177] and may highlight differential coding processes of VTA DA neurons for strong or weak stressful stimuli [166, 178], which is highly consistent with the fine context-detecting functions of VTA DA neurons [21]. It has recently been shown that rats put through a strong stressful paradigm (restrained stress) exhibited increased firing in the VTA while those through a weaker stress paradigm (mild inescapable stress) exhibited decreased activity [179].…”
Section: Neural Circuitsmentioning
confidence: 99%
“…Conversely, the second study showed the opposite effects where phasic activity of VTA DA neurons rescued stress-induced depressive-like behaviour in mice that had undergone chronic mild stress [168]. The discrepancy between the two studies has been discussed [176, 177] and may highlight differential coding processes of VTA DA neurons for strong or weak stressful stimuli [166, 178], which is highly consistent with the fine context-detecting functions of VTA DA neurons [21]. It has recently been shown that rats put through a strong stressful paradigm (restrained stress) exhibited increased firing in the VTA while those through a weaker stress paradigm (mild inescapable stress) exhibited decreased activity [179].…”
Section: Neural Circuitsmentioning
confidence: 99%
“…Alternative approaches to creating depression-like states, such as social defeat or various chronic stress models, may also be used but are more laborious to implement. Again, one way forward is to connect the behavior with the potential brain circuits (67).…”
Section: Measures Of Depression and Anxiety In Rodentsmentioning
confidence: 99%
“…The neural circuits underlying the assignment of valence to environmental stimuli are thought to be highly conserved in the mammalian brain (Janak and Tye, 2015) and are dysfunctional in psychopathologies including anxiety, depression and addiction (Allsop et al, 2014; Etkin and Wager, 2007; Lammel et al, 2014; Mervaala et al, 2000; Tye et al, 2011, 2013). Distributed and interconnected brain structures have been tied to valence coding (Berridge and Robinson, 2003; Namburi et al, 2015a; Nieh et al, 2013), but real-time dynamics within circuits processing valence information during behavioral selection remain largely unexplored.…”
Section: Introductionmentioning
confidence: 99%